Fakor-Faktor yang Mempengaruhi Permintaan Buah Salak Bali (Salacca Zalacca var. ambonensi) oleh Rumah Tanggadi Kota Denpasar, Provinsi Bali - I NENGAH ARI MEDIKANA; I MADE SUDARMA; A.A.A. WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Factors that Affect to Demand of Salak Bali Fruit (Salacca Zalacca var. ambonensi)by Householdin Denpasar City,Bali Province This study aims to know factors that affectdemand quantity ofSalak Bali fruit and magnitude the elasticity of Salak Bali fruit’s demand in Denpasar City. Location of study was atBadung Market, Kreneng Market, Sanglah Market, and Satrya Market thathas been determinated purposively. Populationswas houshold which bought Salak Bali fruit attraditional markets. This study used accidental samplingtechnique.There were 40 samples which has been determined purposively. This study used thetransformed multiple regressionfunctionmodel. Independent variables are X1 (price of Salak Bali fruit), X2(price of orange), X3(price of apple), X4 (price of mango), X5 (quantity of household members), X6 (income of household), and dummy (there are religious celebrations/there aren’t any religious celebrations). The function model is LNY = 2,65 - 1,126 LNX1** - 1,360 LNX2** - 0,643 LNX3** + 0,892LNX4*+ 0,363LNX5**+ 0,590LNX6** + 0.129D**. Factors that affectdemand quantity of Salak Bali fruit are price of Salak Bali fruit, price of orange, price of apple, price of mango, quantity of household members, income household, and situasion.The price elasitcity is elastis, based on cross elasticity both orange and apple are complementary product, while mango is substitution product of Salak Bali fruit. The income elasticity shows that Salak Bali fruits is normal product. Keywords :demand,Salak Bali fruit, Denpasar City, elasticity